PERSAHABATAN DAN KEARIFAN DALAM KUMPULAN CERPEN ANAK AKU, DIA, DAN MEREKA KARYA PUTU AYUB DALAM PROFIL PELAJAR PANCASILA - Etik Titorini; Mukti Widayati; Benedictus Sudiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
One of the literary works that describes forms of human behavior into the value of friendship and contains the potential for local wisdom in each region can be realized in the form of short stories. This research aims to identify and describe the behavior between characters which illustrates the value of friendship which is implemented from local wisdom in the short story collection Anak Aku, Dia and They by Putu Ayub. This research is a qualitative type with a library research approach. Data is collected through documentation techniques, reading techniques and defects. The research results show that the implementation of the values ​​of friendship and local wisdom in the content of short stories includes the special nature of a moment, sharing feelings of joy and sorrow, trust in a secret, honesty over instincts in one's conscience, and the urgency of helping each other in all matters. The depiction of the value of friendship from the existence of local wisdom in each region has been realized in the content of the short story through the actions carried out between the characters in a narrative manner.